Gait adaptations in step length and push-off force during walking with functional asymmetry - Baček, Tomislav; Xu, Yufan; Peng, Liuhua; Oetomo, Denny; Tan, Ying (Frontiers in Bioengineering and Biotechnology, 2025)
Human walking is highly adaptable, allowing individuals to maintain efficiency and stability across diverse conditions. However, how gait adapts to functional asymmetry remains poorly understood. This study addresses this gap by employing a within-subject design to isolate the effect of functional asymmetry using a unilateral knee constraint to emulate hemiparetic gait. This approach eliminates inter-individual variability present in previous studies. A dataset of 19 participants walking across 30 conditions was used to examine these adaptations in step length and push-off force in both absolute terms and symmetry metrics. Results reveal that functional asymmetry disproportionately impacts propulsion, with constrained-leg force decreasing significantly at higher speed, while step length symmetry remains stable. This suggests a prioritisation of spatial over kinetic symmetry, likely to optimise walking energetics and maintain anterior-posterior balance. Statistical models demonstrated good within-dataset performance but limited generalisability across dataset predictions, emphasising the challenges of applying models across studies of different designs. These findings highlight critical limitations in applying statistical models trained on healthy persons to patient populations and provide insights into key biomechanical adaptations that could inform individualised biofeedback strategies for hemiparetic patients. Understanding individual compensations for unilateral deficits could help refine rehabilitation interventions that target propulsion deficits and optimise gait symmetry.